2018
DOI: 10.1186/s40104-018-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological adaptation of sheep’s rumen epithelium to high-grain diet entails alteration in the expression of genes involved in cell cycle regulation, cell proliferation and apoptosis

Abstract: BackgroundThe objectives of this study were to characterize changes in the relative mRNA expression of candidate genes and proteins involved in cell cycle regulation, cell proliferation and apoptosis in the ruminal epithelium (RE) of sheep during high-grain (HG) diet adaptation.ResultsTwenty sheep were assigned to four groups with five animals each. These animals were assigned to different periods of HG diet (containing 40% forage and 60% concentrate mix) feeding. The HG groups received an HG diet for 7 (G7, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…In our study, concurrent with OS, the HC diet caused cell death in colonic mucosa through apoptosis as evidenced by increase of bax mRNA expression and decrease of bcl2/bax expression ratio compared with LC. Consistently, epithelial disruption with obvious increase in TUNEL-positive apoptotic cells associated with modulation of bcl2 and bax gene expression have been demonstrated in hind gut (Cecum and colon) and rumen of cattle, sheep and goats fed grain rich diets [ 56 58 ].…”
Section: Discussionmentioning
confidence: 70%
“…In our study, concurrent with OS, the HC diet caused cell death in colonic mucosa through apoptosis as evidenced by increase of bax mRNA expression and decrease of bcl2/bax expression ratio compared with LC. Consistently, epithelial disruption with obvious increase in TUNEL-positive apoptotic cells associated with modulation of bcl2 and bax gene expression have been demonstrated in hind gut (Cecum and colon) and rumen of cattle, sheep and goats fed grain rich diets [ 56 58 ].…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, this method was used to further confirm the effect of P4HA2 on U87 cell proliferation. According to the amount of DNA, the whole cell cycle can be divided into G 0 /G 1 , S and G 2 /M phases ( 15 ). DNA in the G 0 /G 1 phase is diploid, while it is tetraploid in the G 2 /M phase and in between in S phase ( 16 , 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Feeding of high-concentrate diet increases the production of volatile fatty acids (VFAs) in the rumen [10] and decreases the ruminal pH [11]. Abdoun et al [12] reported that when the physiological pH of rumen liquid is 6.5 or lower, the ruminal ammonia is primarily absorbed in the form of NH 4 + .…”
Section: Introductionmentioning
confidence: 99%